2019
DOI: 10.1177/2059799119829429
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant with possibility: The importance of visual data in (re)presenting queer women’s experiences of reproduction

Abstract: In this article, I discuss a queer method for uniting visual sociology, digital sociology, and constructivist grounded theory to conduct innovative research into how lesbian couples experience the transition to first-time parenthood, based on my longitudinal doctoral research in sociology. I first attend to the complex and unexpected unfolding of the research design, which evolved with the needs of the population to move from adapted photovoice interviews to the use of textual-visual online pregnancy journal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…It raises important questions about the extent to which visual methods can serve as an alternative way of seeing for marginalised participants to represent themselves within research and in the social world. While previous research, primarily conducted in democratic Western societies, has highlighted the potential of visual methods to generate social changes (Holland, 2019), it remains unknown as to whether and how research using visual methods in more restrictive contexts, such as China, can empower participants and bring about changes at individual, community, and/or societal levels. Also, previous Western research using visual methods to study sexuality and intimacy has found that the ways in which participants choose to create visual materials may still replicate the broader cultural knowledge and existing images already associated with established norms and values.…”
Section: Visual Methodologies and Different Forms Of Family Displaymentioning
confidence: 99%
See 3 more Smart Citations
“…It raises important questions about the extent to which visual methods can serve as an alternative way of seeing for marginalised participants to represent themselves within research and in the social world. While previous research, primarily conducted in democratic Western societies, has highlighted the potential of visual methods to generate social changes (Holland, 2019), it remains unknown as to whether and how research using visual methods in more restrictive contexts, such as China, can empower participants and bring about changes at individual, community, and/or societal levels. Also, previous Western research using visual methods to study sexuality and intimacy has found that the ways in which participants choose to create visual materials may still replicate the broader cultural knowledge and existing images already associated with established norms and values.…”
Section: Visual Methodologies and Different Forms Of Family Displaymentioning
confidence: 99%
“…The photo-elicitation interview has also been increasingly used as a method. It involves using one or more images in an interview and inviting the participant to discuss these image(s) in relation to personal or sensitive topics, such as those related to sexuality and family (Del Busso and Reavey, 2013; Holland, 2019).…”
Section: Visual Methodologies and Different Forms Of Family Displaymentioning
confidence: 99%
See 2 more Smart Citations
“…When pregnant women do adopt a “risk management” perspective that prioritizes medical authority, this orientation is often portrayed as a form of subjection (literally, adopting the required subjectivity) to governmental discourses associated with health, pregnancy, and motherhood ( Cao, 2014 ; Li, 2011 ; Song et al, 2012 ). There is ample research that describes how the Internet and social media have become important tools through which pregnant women gather information, receive advice, and assert agency (Drentea & Moren-Cross, 2005; Gui et al, 2017 ; Holland, 2019 ), though often as a counterweight to the authority of medical professionals ( Cohen & Raymond, 2011 ).…”
Section: Introductionmentioning
confidence: 99%